2020
DOI: 10.1080/03043797.2020.1849032
|View full text |Cite
|
Sign up to set email alerts
|

First-year engineering students’ mathematics task performance and its relation to their motivational values and views about mathematics

Abstract: This study investigates Finnish, Norwegian, and Swedish first-year engineering students' task performance in mathematics and examines how it relates to their motivational values and beliefs about the nature of mathematics. In a set of seven mathematical tasks, female students outperformed male students, for example, in the simplification of symbolic expressions. Our findings also show that female students set more demanding learning goals for themselves. Further, they expressed higher intrinsic motivational va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
9
0
3
Order By: Relevance
“…The present study is part of a larger project focusing on the transition problem among freshmen engineering students in Finland, Sweden, and Norway. Some results on the Swedish students separately , and all three cohorts jointly (Tossavainen, Rensaa, Haukkanen, Mattila, & Johansson, 2021) have already been reported. The present paper examines students at a Norwegian university and provides some means to compare the outcome of the upper secondary mathematics education in Norway and Sweden.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The present study is part of a larger project focusing on the transition problem among freshmen engineering students in Finland, Sweden, and Norway. Some results on the Swedish students separately , and all three cohorts jointly (Tossavainen, Rensaa, Haukkanen, Mattila, & Johansson, 2021) have already been reported. The present paper examines students at a Norwegian university and provides some means to compare the outcome of the upper secondary mathematics education in Norway and Sweden.…”
Section: Introductionmentioning
confidence: 90%
“…Our theoretical framework represents this approach by combining the expectancy-value theory with a categorization of epistemological beliefs about the nature of mathematics. A conceptual framework offers such flexibility to combine theories (Lester, 2009), and this particular combination has successfully been done in previous works (Tossavainen, Rensaa, Haukkanen, et al, 2021;Tossavainen, Viholainen, Asikainen, & Hirvonen, 2017).The epistemological beliefs concern the structure, quality, certainty, but also the source of mathematical knowledge (Hofer & Pintrich, 1997). In Germany, Grigutsch, Raatz, and Törner (1998) studied mathematics teachers' beliefs, identifying four categories of beliefs or orientations to mathematics.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…All relevant questions with the numbering used in the questionnaire are given in the following section when the results are presented. The same questions with minor modifications have been tested and used in several earlier studies (Viholainen et al, 2014;Tossavainen et al, 2017;Tossavainen et al, 2020;Tossavainen, et al, 2022). For the analyses, sum variables were computed for each type of epistemological belief and each motivational value as the mean of the two corresponding scales.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the compulsory courses in the engineering programs require certain mathematical concepts and skills, which can be offered as part of mathematics courses before or during the engineering courses. Nevertheless, Tossavainen et al (2020) indicated that new entrance students at engineering programs are often unaware of how mathematically demanding their course would be. Their previous negative attitudes towards mathematics and the insufficient previous information led them to believe that they have chosen a course, where the mathematics would not be necessary.…”
Section: Literature Reviewmentioning
confidence: 99%